A CLINICAL STUDY OF ROOKSHANA POORVAKA VIRECHANA KARMA IN PRE-DIABETES W.S.R. TO STHOULYA (AYUSHDHARA, 2016)
We are in the era where human is running in short of time in order to achieve his goals and to fulfil his worldly luxurious desires and due to the sedentary life-style, a significant increase in the prevalence of obesity is found in almost all the age groups in the past few decades. Obesity is the major risk factors for numerous chronic diseases like diabetes mellitus.Pre-diabetes is the precursor stage to diabetes mellitus in which not all of the symptoms required to label a person as diabetic are present, but blood sugar levels are at borderline or little higher than normal range but not high enough to diagnose as diabetes.The management of Prameha Poorvarupa is explained as Ubhayatashodhana specially in Madhyamvayas. In metropolitan cities like Bangalore person’s life style and food habits causes vitiations of Pitta Dosha. And Virechana is the ultimate kind of Shodhana In Pittaja Vikaras. Hence Vriechana is chosen As Shodhana procedure and to conduct Shodhana. Before conducting Shodhana Rookshana is to be done As Poorvakarma In Mamsala, Meduraa, Bhurishlema And Vishamagni Person.Hence, the study conducted here is in 10 Madhyam Vayas and Pre-diabetes patients, who were subjected to Triphaladi Udvartana which is discussed as Apatarpana yoga in Santarpaniya Adhyaya followed by Virechana. Statistically highly significant results were found in - Ati Trishna, Nidradhikyata, Sweda Adhikya, Angagouravata and Alasya and the objective parameters- body weight, BMI, circumference of hip, abdomen and thigh, skin fold thickness of biceps and triceps (p=